Financial Acountability in Nepal : A Country Assessment - World Bank (Washington, DC, 2013)
This document assesses the quality of financial accountability and transparency in Nepal and makes recommendations for improvement. The financial accountability assessment is a joint exercise of His Majesty's Government of Nepal (HMGN) and the World Bank, with strong participation by donor partners as well as private agencies, non-government agencies, private sector, oversight agencies, and donor partners. the review concludes that the lack of compliance and poor implementation of the regulations is the single most important problem that affects public sector financial accountability in Nepal. With respect to public funds, the report reviews the Government's budgeting, financial planning, cash flow management, accounting and financial reporting, at the central and local government level. It also reviews the standards and practices of the external oversight agencies--the Office of the Auditor General, the Public Accounts Committee, the Commission for the Investigation of Abuse of Authority, the Judicial Council, and the Transparency Internal of Nepal. It assesses what it would take to qualify the country for programmatic lending or budgetary support in replacement of individual project lending. With respect to the private sector, the report examines accounting and auditing standards and practices, the development of the Institute of the Chartered Accountants of Nepal, the demand for, and the supply and training of accountants and auditors. It also examines the accountability in the financial ector that includes banks, finance companies, insurance companies, and cooperative societies and unions. The report also assesses the framework for corporate governance and reviews the activities of the Registrar of Companies, the Securities Exchange Board, and the Stock Exchange. With respect to nongovernmental sector, it examines the financial accountability aspect of nongovernmental organizations.